Implementation of P5 Activities Based on Local Wisdom Aceh Culture Teacher Learning Products in Elementary Schools - Hasbi, Ajharuddin; Sari, Siti Mayang; Akmaluddin, Akmaluddin (FKIP - Universitas Riau, 2025)
This study aims to analyze the implementation of the Pancasila Student Profile Strengthening Project (P5) activities based on local wisdom of Acehnese culture in producing learning products by teachers in elementary schools. The Merdeka Curriculum encourages the implementation of P5 as an effort to shape students' character according to Pancasila values ​​through a contextual project approach. Acehnese local wisdom, which is rich in cultural values ​​and Islamic traditions, has great potential to be integrated into P5 activities to strengthen students' cultural identity and 21st-century skills. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The subjects of the study were elementary school teachers who had implemented P5 based on local wisdom. The results of the study showed that the integration of local culture into P5 encouraged teachers to create more innovative and contextual teaching materials, such as modules, learning media, and student projects based on Acehnese culture. The obstacles faced included limited resources and lack of training. However, with collaborative strategies and school support, teachers were able to produce meaningful learning products. This study contributes to the development of project-based learning and the preservation of local culture through elementary education.